IMPLEMENTATION OF THE MERDEKA LEARNING CURRICULUM IN INCREASING THE QUALITY OF LEARNING AT SMPN 32 BEKASI - Nyai Ajeng Ratna Suminar Maksudi (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
ABSTRACTThe purpose of implementing the independent curriculum at SMPN 32 Bekasi is to improve the quality of learning for students in developing their abilities and increasing innovative creativity so that students can develop according to the abilities contained in the students. The Merdeka curriculum teaches students independence in learning and cultivating innovative thought patterns.The method used in this study is descriptive qualitative. Where the research wasconducted at SMPN 32 Bekasi, data collection techniques used are observation, interviews, documentation, and literature. Validity of data using triangulation. The data has been collected and analyzed using interactive models through data reduction, data presentation, and conclusions.The results of this study independent curriculum in SMPN 32 Bekasi can be applied or implemented to the student learning module. Teachers and students work together to be able to apply and adapt to this new curriculum. Students can innovate and channel their creativity freely according to their abilities. An Independent curriculum can improve the quality of learning so that the effectiveness of the ability and competence of teachers in the subjects they mastered. Keywords: Implementation, Curriculum, Independent Curriculum, Learning Quality